Recurrent stroke in a reproductive age women with patent foramen ovale - Jing Ye; Yujia Yang; Li Tang; Li He; Muke Zhou (BMC, 2024)
Abstract Background Patent foramen ovale (PFO) is a known cause of ischemic stroke in young adults and combined oral contraceptives (COCs) are widely used by women of reproductive age. If young women with PFO are taking COCs, they may be subjected to a synergistic increase in the occurrence of stroke, though reports of ischemic stroke in this population are rare. We report a woman of reproductive age who was taking COC suffered repetitive ischemic strokes before a patent foramen ovale (PFO) was detected and closed, which may raise concerns in this field. Case presentation A 31-year-old woman presented to the emergency department with sudden-onset right upper- and lower-limb weakness and dysarthria for 1 hour, whose only risk factor of stroke was oral contraceptive use. On admission, she was alert with left gaze deviation, dysarthria, and right-sided hemiplegia. Her symptoms improved after receiving the revascularization therapy. About 24 hours later, her left eye experienced sudden painless vision loss. Then the PFO with a substantial right-to-left shunt was detected and then she received a trans-catheter closure of the defect. Over 3 months of follow-up, there were no signs of stroke, but visual loss persisted. Conclusion This case of disabling stroke raises concerns regarding optimal management in primary and secondary prevention of stroke in young women on COCs with additional risk factors of stroke.